SIX MAIN PRINCIPLES FOR QUALITY LEARNING BASED ON TA’LĪM AL-MUTA’ALLIM ṬORĪQ AL-TA’ALLUM - Adib Rifqi Setiawan (Religio Education, 2021)
This article examines the requirements for quality learning, that is based exclusively on the nadzom “alālā” that wrote by Burhān al-Dīn al-Nu’mān ibn Ibrōhīm al-Zarnūjī in his treatise entitled “Ta’līm al-Muta’allim Ṭorīq al-Ta’allum”. The quantitative research descriptive studies category used in this article and the results are described based on content analysis technique. It reveals that quality learning has six things dependency: ingenious acumen, fervent desire, resilience, sufficent sustenance, guidance of a teacher, and length of time. The best way to test of any educational factors, of course, is develop instruments to measure quantitatively. The development of instruments is yet to do.